1980
DOI: 10.1007/bf01888615
|View full text |Cite
|
Sign up to set email alerts
|

Gastroduodenal erosions in Crohn's disease

Abstract: Gastroduodenal erosions were observed endoscopically and shown by double-contrast radiology in nine of 38 patients who had established Crohn's disease elsewhere in the intestinal tract. One of the nine patients was known to have duodenal involvement by Crohn's disease, but in the other eight there was no clinical suspicion of upper gastrointestinal disease. The possible significance of this finding is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Barium meal studies and upper endoscopy complement each other in establishing a diagnosis of gastroduodenal involvement in Crohn's disease (28). Upper endoscopy and barium meal both dem-onstrated mucosal changes in seven of the 10 cases reported in this study.…”
Section: Discussionsupporting
confidence: 54%
“…Barium meal studies and upper endoscopy complement each other in establishing a diagnosis of gastroduodenal involvement in Crohn's disease (28). Upper endoscopy and barium meal both dem-onstrated mucosal changes in seven of the 10 cases reported in this study.…”
Section: Discussionsupporting
confidence: 54%
“…a bamboo-jointlike appearance ( while Laufer et al reported that the observation of multiple superficial gastric erosions on double contrast radiography of the stomach was a characteristic finding in the early stage of CD [30]. Subsequently, most reports on gastric lesions in CD patients have focused on erosive lesions in the antropyloric region, the frequency of which was reported to be 24-73% by 1990 [8,31,32]. In CD patients, erosion is frequently observed in the antropyloric region; the characteristics of the erosion include flat reddening, verrucous gastritis and aphthoid erosion-the morphologic features of which include circular and irregularly shaped longitudinally aligned areas of erosion.…”
Section: Gastric Lesionsmentioning
confidence: 99%
“…Other causes of gastric erosions include alcohol, viral infections, Crohn disease, hemorrhagic gastropathy, and iatrogenic trauma (4,(50)(51)(52)(53)(54)(55). Surprisingly, erosions are infrequently seen in patients with H pylori gastritis (18).…”
Section: Figure 10mentioning
confidence: 99%